CHILD URBAN MOBILITY: THE IMPORTANCE OF HOME-SCHOOL TRAVEL TO CHILD CITIZENSHIP (Publicatio UEPG: Ciências Sociais Aplicadas, 2023)
Urban mobility is a child’s right, however, the experience of walking the streets has become rarer to Brazilian children, mostly to the ones who live in urban areas. Therefore, home-school commuting is the closest contact these children have with urban spaces, given its daily recurrence. It is through mobility that these children participate in the communities they inhabit. They become citizens. In this sense, we seek to understand how the experience lived by children in their home-school commuting are important to the construction of their citizenship. Thus, through an ethnographic study at a socially vulnerable neighborhood of Recife — a city within the state of Pernambuco — we could comprehend that through home-school commuting children socialize with their peers and other citizens along the surroundings of their schools and exercise active citizenship. On the other hand, we could also observe that children’s urban rights are not respected in regard to urban mobility.